Chapter From the Virtues of Argumentation to the Happiness of Dispute - Mastroianni, Bruno (Communication and Philosophical Cultures. Researches and Instruments, 2021)
Efficient debate training should develop the ability to manage real discussions and not just be a laboratory for ideal talks. In this regard, the perspective of the virtues of argumentation is particularly suitable. Virtuous arguing allows the recognition of the other's difference - the contemplation of difference. Using Aristotelian ideas of contemplation as happiness opens up the possibility of accepting the arguers' imperfections and configure disputes suitable for producing shared outcomes, making them genuinely deliberative.